Planning of Development Upper Structure of the Rorotan Labor Intensive Flats North Jakarta - Winanto Winanto (Jakarta Global University, 2022)
The planning for this 16-storey building is a re-planning of the construction project for the Padat Karya Flats located in Rorotan, North Jakarta. This building planning is carried out based on the procedure for calculating concrete structures for buildings (SNI 2847:2019). The data for this building plan was obtained from the architect planning the construction of the Rorotan Solid Work Flats. The design of the superstructure includes the planning of slab, beam and column elements; The scope of the discussion includes calculation of loading, calculation of initial dimensions, ETABS analysis, control of analysis results, final dimension design and reinforcement, design drawings. The material used is reinforced concrete with a concrete quality of fc'35 Mpa fc’40 Mpa and fy 420 Mpa. The basics of planning refer to SNI 2847:2019 Procedures for Planning Concrete Structures for Buildings. And SNI 1726:2019 Earthquake Resistance Planning for Building Structures. Structural analysis using ETABS program with dynamic analysis of Response Spectrum.The keyword Multi-storey building, planning, superstructure, slab, column, beam.